2011
DOI: 10.1179/016164110x12767786356471
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effectiveness of azithromycin in prevention of postlaminectomy epidural fibrosis

Abstract: Immune system plays critical roles in tissue repair and fibrogenesis. Results of our study demonstrated that azithromycin application reduced formation of peridural fibrosis in experimental laminectomy model in rats. Further studies with different dose regimes and different application routes are required to carry these results to an advanced level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Currently, the exact mechanisms that underlie the development of epidural fibrosis after laminectomy are still uncertain. It has been found that immune and inflammatory reactions play key roles in the formation of epidural fibrosis [ 33 , 34 ]. After being stimulated by various immune cytokines, fibroblasts tend to proliferate extensively, produce collagen, and release extracellular matrix, which ultimately results in the formation of epidural scar adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the exact mechanisms that underlie the development of epidural fibrosis after laminectomy are still uncertain. It has been found that immune and inflammatory reactions play key roles in the formation of epidural fibrosis [ 33 , 34 ]. After being stimulated by various immune cytokines, fibroblasts tend to proliferate extensively, produce collagen, and release extracellular matrix, which ultimately results in the formation of epidural scar adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Local immune response is considered critical for each type of post‐operative skeletal fibrosis and some immunosuppressant drugs used to prevent post‐operative skeletal fibrosis have achieved success, including rapamycin, tacrolimus, pimercrolimus, azithromycin, methotrexate and cyclosporin A . Results showed that they could prevent post‐operative skeletal fibrosis by inhibiting fibroblast proliferation, suppressing interleukin 2 (IL‐2) and TGF‐β1 expression, regulating miR‐429 and RhoE expression and activating autophagy and the ER stress signaling pathway …”
Section: Current Therapies For Post‐operative Skeletal Fibrosismentioning
confidence: 99%
“…It has been well established that epidural fibrosis formation is a complex multi‐step process associated with a significant reduction in the tissue cellularity and excessive deposition of collagen, fibronectin and dermatan sulphate (DS) . Accumulated evidence has shown that specific cytokines like interleukin (IL)‐2, transforming growth factor (TGF)‐ β and IL‐4 significantly promote the progression of fibrogenesis . In the fibrotic process, fibroblasts are activated by these cytokines, produce multiple collagens and form permanent fibrotic scars …”
Section: Introductionmentioning
confidence: 99%